2003
DOI: 10.1038/sj.onc.1206636
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of FGF receptor-2 expression by transcription factor E2F-1

Abstract: Fibroblast growth factors (FGF) and their receptors play an important role in cell proliferation, angiogenesis and embryonal development. In this study, we show that expression of the FGF receptor-2 (FGFR-2) protein is induced in the mid-to-late G1 phase of the cell cycle in serum-starved mouse NIH3T3 cells released from starvation. Transcription of mouse FGFR-2 was activated by E2F-1. Analysis of various mouse FGFR-2 promoter mutant constructs showed that a sequence located þ 57/ þ 64 downstream of the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…Thus, the birth size would determine the number of growth receptors present and the initial growth rate during the sizer phase. A recent experiment (Tashiro et al, 2003) showed that FGF receptor-2 transcription was constant during early portions of the cell cycle where cell growth would normally occur but was induced in the mid-to-late G1 phase of the cell cycle in serum-starved mouse NIH3T3 cells. Other growth signaling proteins that localize to the cell membrane, such as PI 3-kinase and PDK1, are also candidate proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the birth size would determine the number of growth receptors present and the initial growth rate during the sizer phase. A recent experiment (Tashiro et al, 2003) showed that FGF receptor-2 transcription was constant during early portions of the cell cycle where cell growth would normally occur but was induced in the mid-to-late G1 phase of the cell cycle in serum-starved mouse NIH3T3 cells. Other growth signaling proteins that localize to the cell membrane, such as PI 3-kinase and PDK1, are also candidate proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, FGFR1 amplification and overexpression has been revealed as key in resistance to adjuvant tamoxifen (Turner et al, 2010b), and integrative profiling has shown FGFR2 overexpression to be a promising therapeutic target in triple-negative breast cancer (Turner et al, 2010a). Accordingly, the expression of FGFR1 and FGFR2 is partially regulated by E2F1 (Tashiro et al, 2003;Kanai et al, 2009). Furthermore, targeting FGFR-mediated signaling that acts in an autocrine manner in a subset of breast cancers of poor prognosis has been shown to impair tumor outgrowth and metastasis (Dey et al, 2010).…”
Section: Effect Of 17be2 Through Eramentioning
confidence: 99%
“…An increase of the cyclin D1 level determines an accumulation of the hyperphosphorylated form of pRb, leading to pRb inactivation and therefore to the release of a transcriptionally active E2F-1 factor, responsible for the activation of the fibroblast growth factor receptor 1 (FGFR-1) promoter. E2F-2 and E2F-3, the other two members of the E2F family regulated by pRb, can also increase FGFR-1 promoter activity, whereas E2F-4 and E2F-5, and consequently their negative regulators pRb2/p130 and p107, do not seem to be involved in the modulation of FGFR-1 expression (Tashiro et al, 2003).…”
Section: Involvement Of Rb Family In Angiogenesis C Gabellini Et Almentioning
confidence: 99%